Job rotation and work-related musculoskeletal disorders: a fatigue-failure perspective. Issue 4 (2nd April 2020) - Mehdizadeh, Amir; Vinel, Alexander; Hu, Qiong; Schall, Mark C.; Gallagher, Sean; Sesek, Richard F.
Abstract: Job rotation is an organisational strategy that can be used, in part, to reduce occupational exposure to physical risk factors associated with work-related musculoskeletal disorders (MSDs). Recent studies, however, suggest that job rotation schedules may increase the overall risk of injury to workers included in the rotation scheme. We describe a novel optimisation framework evaluating the effectiveness of a job rotation scheme using the fatigue failure model of MSD development and a case study with real injury data. Results suggest that the effect of job rotation is highly-dependent on the composition of the job pool, and inclusion of jobs with higher risk results in a drastic decrease in the effectiveness of rotation for reducing overall worker risk. The study highlights that in cases when high-risk jobs are present, job redesign of those high risk tasks should be the primary focus of intervention efforts rather than job rotation. Practitioner summary: Job rotation is often used in industry as a method to 'balance' physical demands experienced by workers to reduce musculoskeletal disorder (MSD) risk. This article examines the efficacy of reducing MSDs through job rotation using numerical simulation of job rotation strategies and utilising the fatigue failure model of MSD development.